Impacts of Migration and Cultural Integration in Thai Society - Sirikul, Konlawid (Thai Social Science Journal, 2025)
This article examines the impacts of migration and the process of cultural integration within Thai society from an ethnographic perspective, emphasizing power relations, identity transformation, and cultural adaptation amid ethnic and cultural diversity. The study analyzes the context of both internal and international migration, focusing on migrant groups that play significant roles in Thailand’s current economy and society, as well as the factors influencing settlement patterns and ethnic distribution. The economic impacts of migration are dual-faceted: migration contributes to labor market enhancement and economic growth at local and national levels, while also exerting pressure on infrastructure and local employment opportunities. Social and cultural effects include the emergence of dynamic cultural exchanges and diversity, yet accompanied by tensions and conflicts, especially where power imbalances and cultural discrimination persist. Policy recommendations highlight the importance of participatory decision-making involving migrant and ethnic communities, fostering genuine understanding and acceptance of cultural diversity. Development of infrastructure and public services tailored to local contexts, alongside promoting cooperation among government, civil society, and local communities, are essential to building a strong and sustainable multicultural society in contemporary Thailand.